Assessment of ploidy and genome constitution of some musa balbisiana cultivars using DArT Markers - Butardo, Nilda G.; Paniagua, Humberto Gomez; Jansen, Hans; Dolezel, Jaroslav (2011)
The Philippines is one of the centers of origin and diversity for bananas. There is an endless range of names and synonyms for cultivars, thus the major constraint in banana and plantain research is on proper identification and classification. Musa balbisiana is grown extensively and considered endemic in the Philippines. However, there are opposing views as to the genomic constitution of cultivars. Philippine and other Asian Musa experts claimed that Philippine ‘Saba’ group is of the triploid B but American and European Musa workers denied the existence of such and consistently claimed that it is hybrids of A and B genomes. The objective of the study was to determine if Diversity Array Technology (DArT) analysis can efficiently verify the genome constitution of the Musa cultivars in question. Twenty-four Philippine Musa cultivars were subjected to flow cytometry analysis for ploidy confirmation and DArT analysis of molecular characterization. Results of the flow cytometry analysis confirmed the triploidy of the Philippine ‘Saba’ group while the molecular data showed that some DArT markers were specific for the B genome such as that these markers can identify the cultivars with B genome regardless of the presence of A genome. Hence these markers can be used to establish genome identity of the Musa cultivars. Likewise, dendrogram constructed by Mega version 4 clearly separated the BB/BBB cultivars from AA/AAA and AAB cultivars. Moreover, the dendrogram showed that most of these putative BBB cultivars grouped as a separate cluster from the AAA and AAB groups. Bootstrapping all the more enhanced these groupings, and strongly supported the existence of a pure Balbisiana group. These confirmed the Asian claims of the triploid B nature of the Philippine ‘Saba’ group. However, two cultivars namely ‘Inambak’ and ‘Pondol’ (assumed to be of the BBB type) formed a cluster with the AAB (cv’Tindok and Latundan’). This suggests therefore, that these two Phil. Musa cultivars could be AAB unlike the rest of the cultivars claimed to be triploid B.
Keywords: Musa balbisiana